2015
DOI: 10.1097/shk.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Cyclophosphamide Improves Survival in a Murine Treatment Model of Sepsis

Abstract: Sepsis is a complex medical condition characterized by a systemic inflammatory response in the setting of infection. We hypothesized that combining antibiotics plus an immunosuppressant would protect against the morbidity and mortality of polymicrobial sepsis in mice better than antibiotics alone. We used a murine cecal ligation and puncture model in which mice were treated either with imipenem plus cyclophosphamide or imipenem alone. Titration to a low cyclophosphamide dose revealed that combination therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…The CS and CLP models are similar in that they induce severe intra-abdominal infections via exposure to endogenously-derived polymicrobial bacteria. Indeed, many have found that antibiotic administration after CLP significantly improves survival (15, 17, 18, 21), especially in the young (13). When administration of antibiotics was delayed until 12 hours after CLP and given every 12 hours for 5 days, animals with IL-6 levels >14,000 pg/mL at 6 hours were unable to be rescued (14).…”
Section: Discussionmentioning
confidence: 99%
“…The CS and CLP models are similar in that they induce severe intra-abdominal infections via exposure to endogenously-derived polymicrobial bacteria. Indeed, many have found that antibiotic administration after CLP significantly improves survival (15, 17, 18, 21), especially in the young (13). When administration of antibiotics was delayed until 12 hours after CLP and given every 12 hours for 5 days, animals with IL-6 levels >14,000 pg/mL at 6 hours were unable to be rescued (14).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to topoisomerase II inhibitors, such as anthracyclines, a protective effect in several models of infection has also been recently documented for topoisomerase I inhibitors . The DNA‐damaging chemotherapeutic drug, cyclophosphamide, also improves survival in a mouse model of sepsis, when used at low concentrations in combination with a broad‐spectrum antibiotic . At least in the case of topoisomerase II inhibitors (anthracyclines), ATM is critical for the protection, as discussed before.…”
Section: Dna Damage Recognition In Host–pathogen Interactionsmentioning
confidence: 78%
“…53 In addition, local lidocaine or bupivacaine has been used at the incision site in surgical models of sepsis either alone or in conjunction with systemic analgesics. 9,43,89 Studies evaluating analgesic efficacy in sepsis have used variable drugs, dosages, and durations of administration (Figure 2). Generally, 2 d of routine analgesia followed by as needed administration are required for rodent laparotomy at this institution.…”
Section: Surgical Models Of Sepsismentioning
confidence: 99%